The CAR T Cell Story - Norman Russkamp; Thorsten Zenz (healthbook TIMES. Oncology Hematology)
During the entire 20^th^ century, chemotherapy and irradiation were the mainstay of non-surgical cancer treatment. In the past 20 years, however, cancer immunotherapy has been revolutionizing the field of oncology with ever-increasing pace. During this time, various molecular pathways have successfully been exploited to re-direct the immune system to fight cancer. This shift of treatment paradigms was acknowledged by the Nobel committee, which awarded the 2018 Nobel Prize in Physiology or Medicine to James Allison and Tasuku Honjo for their discoveries leading to the development of checkpoint inhibitors.^1^ A different approach, however, has gained widespread attention inside as well as outside the medical community: the regulatory approval of chimeric antigen receptor (CAR) T cells for the treatment of leukemia and lymphoma in 2017. While the adoptive transfer of genetically engineered human cells in clinical routine has been limited to individual indications, the unprecedented efficacy of genetically modified T cells in refractory patients was inconceivable a few years ago. The groundwork for the clinical implementation of CAR T cells was laid in the past three decades in terms of progress that was made in the fields of immunology as well as in cellular and gene therapy. Here, we provide a brief overview of fundamental discoveries, from basic to translational research, that ultimately led to the clinical approval of CAR T cells for the treatment of cancer patients.